2016
DOI: 10.1016/j.cej.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel adsorptive ultrafiltration membranes derived from polyvinyltetrazole-co-polyacrylonitrile for Cu(II) ions removal

Abstract: Novel adsorptive ultrafiltration membranes were manufactured from synthesized polyvinyltetrazole−co−polyacrylonitrile (PVT−co−PAN) by nonsolvent induced phase separation (NIPS). PVT−co−PAN with various degree of functionalization (DF) was synthesized via a [3 + 2] cycloaddition reaction at 60 o C using a commercial PAN. PVT−co−PAN with varied DF was then explored to prepare adsorptive membranes. The membranes were characterized by surface zeta potential and static water contact angle measurements, scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The issue of water pollution is becoming increasingly serious throughout the world. Industrial wastewater is a major source of water pollution because it contains organic contaminants, such as benzene, toluene, and arsenic, or heavy metals, such as copper (Cu), nickel (Ni), lead (Pb), chromium (Cr), and zinc (Zn) . Membrane‐separation technologies, such as ultrafiltration, are the most common method for industrial wastewater treatment, not only because they are environmentally friendly but also because of their wide applicability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of water pollution is becoming increasingly serious throughout the world. Industrial wastewater is a major source of water pollution because it contains organic contaminants, such as benzene, toluene, and arsenic, or heavy metals, such as copper (Cu), nickel (Ni), lead (Pb), chromium (Cr), and zinc (Zn) . Membrane‐separation technologies, such as ultrafiltration, are the most common method for industrial wastewater treatment, not only because they are environmentally friendly but also because of their wide applicability .…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylonitrile (PAN) is also a common microfiltration and ultrafiltration membrane material by virtue of its chemical stability, thermal stability, low cost, and tolerance to organic solvents . The molecular structures of PVDF and PAN are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Within the current technologies for the removal of metal ions, membrane technologies (electrodialysis, nanofiltration, ultrafiltration, and polymer‐assisted ultrafiltration [PAUF] ) are common. In addition, solid–liquid separation techniques are used to remove pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyltetrazoles (PVTs) [30][31][32] and its derivatives have attracted broad attention because of their interesting properties (high thermostability, biological activity and good solubility) and wide applications (polyelectrolytes, distinctive complex, dynamite and biocompatible material). However, the vinyltetrazole 33 is not a common monomer for commercial source because of the difficult synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…By using simple and efficient synthesis, the cyano groups in PAN can react with sodium azide (NaN 3 ) to prepare PVT [30][31][32]37,38 with various molecular weights. Matyjaszewski et al 39 reported welldened PAN and PAN-co-PSt prepared by atom transfer radical polymerization (ATRP).…”
Section: Introductionmentioning
confidence: 99%